Pregnancy during a pandemic of coronavirus infection COVID-19 risks and effects on the unborn child (Texas Journal of Medical Science, 2023)
Pregnancy is a special time that is full of excitement and hope in every woman’s life. But for expectant mothers, fear, anxiety, and uncertainty because of the current COVID-19 status will turn this happy time into a cloud. Pregnant women with Covid-19 are less tolerant of both the pregnancy itself and the coronavirus infection. By complicating each other, they increase the risk of maternal mortality by a significant amount. However, if a pregnant woman is infected with Covid-19, the risk of severe infection increases. Not least because during pregnancy, physiological changes occur in the expectant mother's body that suppress the immune response - in order to prevent rejection of the fetus, which is "still a half-foreign implant."